PENGATURAN HUKUM TERHADAP ANAK PELAKU MUCIKARI PROSTITUSI ONLINE MELALUI APLIKASI MICHAT (STUDI PUTUSAN NOMOR 5/PID.SUS-ANAK/2021/PN CRP) - Afifah Fauzziyyah; Fitri Z, Yenny (IAIN Ambon, 2025)
The phenomenon of prostitution can be said to be a crime, where prostitution is an activity and action that violates the rules and norms that apply in society, including deviant acts. Now in this digital era, actions are developing, both in terms of perpetrators and practices. Prostitution comes from the Latin pro-stituere or pro-stauree, which means allowing oneself to commit adultery, committing prostitution. While prostitution is a prostitute or prostitute. The crime of online prostitution is a form of crime in cyberspace, where sexual services are provided via the internet. Online prostitution is a type of cybercrime that happens in the online world. It is considered a harmful activity. This crime can involve both adults and young people. The study aims to look at how criminal punishments are applied to children who break the law, based on the decision from the Curup District Court, Case Number 5/Pid.Sus-Anak/2021/Pn Crp. The research uses a normative approach, which means it focuses on legal rules and uses legal documents as the main source of information. Keywords: online prostitution, michat application, minors